2004
DOI: 10.1016/j.virol.2003.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analyses of the core domain of Avian Leukemia and Sarcoma Viruses integrase: critical residues for concerted integration and multimerization

Abstract: During replicative cycle of retroviruses, the reverse-transcribed viral DNA is integrated into the cell DNA by the viral integrase (IN) enzyme. The central core domain of IN contains the catalytic site of the enzyme and is involved in binding viral ends and cell DNA as well as dimerization. We previously performed single amino acid substitutions in the core domain of an Avian Leukemia and Sarcoma Virus (ALSV) IN [Arch. Virol. 147 (2002) 1761]. Here, we modeled the resulting IN mutants and analyzed the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…Moreover, for the aberrant ends not inserted at the canonical CA, the insertion event does not generate the 5-to 6-bp duplication in the host genome that is characteristic of the normal concerted insertions that involve integrase. Taken together, the data support, but do not prove, a model in which the normal end is inserted by integrase in a reaction similar to the single-end insertions seen in in vitro integrase assays (13,19) and the aberrant end is inserted into the host genome by host enzymes. However, in an RSV-based in vitro integration assay that led to efficient concerted integration events with a substrate with a wild-type sequence at the ends, mutating the concerted CA reduced the concerted integrations and did not appear to produce single-end insertions (1).…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, for the aberrant ends not inserted at the canonical CA, the insertion event does not generate the 5-to 6-bp duplication in the host genome that is characteristic of the normal concerted insertions that involve integrase. Taken together, the data support, but do not prove, a model in which the normal end is inserted by integrase in a reaction similar to the single-end insertions seen in in vitro integrase assays (13,19) and the aberrant end is inserted into the host genome by host enzymes. However, in an RSV-based in vitro integration assay that led to efficient concerted integration events with a substrate with a wild-type sequence at the ends, mutating the concerted CA reduced the concerted integrations and did not appear to produce single-end insertions (1).…”
Section: Discussionmentioning
confidence: 53%
“…Analyses of various proviruses have revealed that the length of target site duplication, though varying from 4 to 6 bp among the different retroviruses examined, is invariant for each particular retrovirus [12], [23], [39]. The high fidelity of the direct repeat length supports the notion that IN multimers form a stable complex with viral and target DNA and catalyze coordinated processing and integration of the two viral DNA ends [30], [33], [40], [41], [42]. In addition, reaction conditions in vitro and in vivo that promote uncoordinated integration of the two ends often produce deletions and duplications of various lengths in the target DNA [25], [26], [27], [28], [29], [31], [39], [43].…”
Section: Discussionmentioning
confidence: 99%
“…1). The isolated products were ligated and subsequently used to transform MC1061/P3 cells (Invitrogen) (41,42). The donor-target junctions of individually isolated recombinants were sequenced using HIV-1 U3 and U5 sequence-specific primers (46).…”
Section: Methodsmentioning
confidence: 99%